Effects of Anapana Meditation Technique in School Children - Pandey, Mukti Prasad (Nepal Journal of Multidisciplinary Research, 2022)
Ānāpāna is a type of meditation in which the incoming and departing natural breaths are used as meditation objects. S.N. Goenka, a vipassana teacher from the Ledi Sayadaw lineage, has created a special meditation course for schoolchildren called 'npnaĀnāpāna,' which has a good impact on their academic and behavioral outcomes. This article seeks to examine the influence of Ānāpāna techniques among practitioners using primary and secondary data. To assess the effect of ānāpāna, a structured questionnaire set was designed to seek first-hand information from 240 students from two secondary schools of Kathmandu Valley. Students who have already taken ānāpāna courses and continued their practice are chosen for the study. Analyzing the effects of ānāpāna in nine different clusters, the chi-square test is applied at a five per cent level of significance to justify the result. The study showed that the ānāpāna technique helps improve students' study habits and academic performance. In addition to that, regular ānāpāna practice would be helpful to improve physical as well as mental health, reduce anger, improve relationships with friends, family members, and their relatives. The Chi-square test result also showed a significant association with regular ānāpāna practice in all nine variables.